A broadband reconfigurable antenna with parasitic water radiation Array. Issue 10 (30th July 2021) - Yang, Yuejie; Lu, Taoming; Yang, Helin; Wu, Jiong; Shen, Zhaoyang; Li, Yujun; Hua, Lina; Li, Shangru
Abstract: This article introduces a wideband pattern reconfigurable antenna made of seawater. A special funnel‐shaped metal structure is used for feeding to increase the bandwidth of the antenna. The antenna‐design refers the electronically steerable parasitic array radiator antenna principle, and arc‐shaped water columns are introduced around the seawater monopole antenna to operate as parasitic passive oscillators. These parasitic elements turn the omnidirectional antenna into a directional antenna. The proposed antenna has more than one mode. When the number of parasitic elements is 2, 3, and 4, it respectively corresponds to three different working modes: dual‐beam radiation, wide‐angle radiation, and directional high‐gain radiation. And in all these three modes, changing the position of the parasitic elements can achieve 360° beam‐sweeping in the 1.66 2.78 GHz. A prototype is fabricated and verified, and the experimental results are in good agreement with the simulated results. The antenna is filled with seawater when in use, and the weight can be reduced by draining the seawater when not in use. There is great application potential in the field of maritime communications.